Preparation of activated carbon electrodes from orange peel biomass with various separator materials for supercapacitor applications - Alamin, Rahmatan Lil; Awitdrus, Awitdrus (Indonesian Physics Communication, 2025)
Activated carbon electrodes from orange peel biomass materials for supercapacitor applications with variety of type separator have been prepared. Activated carbon was prepared by pyrolysis process at 800° under N2 gas envinroment. Electrochemical characterization was tested on avariety of separators, i.e, JR-800-W (using Whatman paper number 40), JR-800-E (using eggshell membrane, and JR-800-O (using orange fruit membrane). The results of chemical measurement for the cyclic voltammetry method on the three samples are capacitance values of 191.82 F/g on JR-800-W, 115.08 F/g on JR-800-E, and 94.17 F/g on JR-800-O. The capacitance value in the galvanostatic charge-discharge method are 174.24 F/g with IR drop of 0.067 for sample JR-800-W, 133.22 F/g with IR drop of 0.14 for sample JR-800-E, and 116.8 F/g with IR drop of 0.36 for sample JR-800-O. Whatman paper separators produce good electrochemical properties, indicating the use of separators can affect the performance of activated carbon electrodes for supercapacitor applications.